Stroke as a complication of acute coronary syndrome: questions to the neurologist - Arkuszewski, Michał; Rość-Bereza, Katarzyna; Opala, Grzegorz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Stroke is the most important cause of disability and one of the most important causes of death. About 1.40% of patients with acute coronary syndrome (ACS) suffer from stroke, of which about 2/3 are ischemic strokes. Intracranial hemorrhage is a complication in about 1.43% of patients with myocardial infarction treated with thrombolysis. Dual antiplatelet therapy raises the risk of hemorrhagic complications, however it is not determined whether it raises the risk of intracranial hemorrhage. At present, there are no detailed guidelines for the management of patients with intracranial hemorrhage in the course of the dual antiplatelet therapy after ACS. Every patient with acute stroke should be treated in the stroke unit under supervision of the neurologist. At present, there are no recommendations for the routine use of any kind of neuroprotection in the stroke.